“Então, menina, a marcha é libertadora”: pela vida das mulheres e pela agroecologia – PB - Neves, Laís de Oliveira (2022)
This work presents the alternative made by rural women who flee from the unbridled and deadly logic of heteropatriarchy. Through Agroecology, these women fight for the right to exist. With the aim of presenting the socio-historical role of the March for the Life of Women and Agroecology - PB (20152020), this dissertation is divided into three chapters, in addition to the introductory chapter. In the second chapter, I present, through decolonial feminism, a genealogy of rural women's movements in Paraíba, with the theoretical support of authors such as Alves (2017), Duarte (2014), Ferreira (2010), Serrano (2014) and Sobreira (2017), as well as the social political actions of the Polo da Borborema. In the third chapter, I discuss Agroecology and its dialogues with ecofeminism, through the theorists King (1997), Kunhen (2017), Salleh (1994), Shiva (1993), Silliprandi (2018) and Warren (2000) . Finally, in the fourth chapter, I present the results obtained in the digital survey with the Assessoria Serviços e Agriculturas (ASPTA), as well as the interviews with women who participate in - and constitute the - March, seeking to understand the historical memories, the self-writings and the cultural traits that manifest themselves.